Efektifitas Layanan Bimbingan Kelompok untuk Meningkatkan Kepercayaan Diri Siswa melalui Teknik Menulis Ekspresif pada Siswa Kelas X SMA Negeri 2 Samarinda Tahun Ajaran 2025 - Niken Novita Dewi; Wahyu Widyatmoko; Dwi Sona; Dhanang Suwidagdho (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This research is motivated by students' low self-confidence, demonstrated by a lack of courage to express opinions, participation in learning, and social interaction in the classroom. Self-confidence is an important aspect of students' personal development, influencing their learning success and adjustment. This study aims to determine the difference in students' self-confidence levels before and after being given group guidance services using expressive writing techniques. This research used an experimental research design with a one-group pretest-posttest design. The sample consisted of 8 students selected using a purposive sampling technique. Based on the pretest and posttest data, the mean score before treatment was 74, which is considered low, and after treatment, it showed an increase with a mean score of 84. The paired t-test analysis obtained a significance value of 0.001 <0.05, indicating a significant difference in students' self-confidence levels before and after being given group guidance services using expressive writing techniques for 7 meetings. Thus, group guidance services using expressive writing techniques have proven effective in increasing the self-confidence of 10th-grade students at SMA Negeri 2 Samarinda.